Mobility while Waiting. Survival, Decisions, and Emotions of Migrants at Mexican Border Cities - Fernández Casanueva, Carmen (2024)
The article aims to analyze waiting periods during the mobility of people intending to migrate to the United States of America. It primarily focuses on the moment when people have to make a stop on their journey and wait in four Mexican cities: two at the southern border and two at its northern border. Based on qualitative research using different methods covering a broad period of fieldwork, and interweaving the literature on mobility and waiting, our intention is to demonstrate how migrants live, as well as manage and signify waiting periods during their stay in these cities. In addition, we wish to highlight how the waiting moment is a mechanism to stop mobility towards the United States through an array of strategies devised by the Mexican state. However, migrating people continue the movement, making decisions and surviving while waiting. That is, far from inducing paralysis and withdrawal, waiting moments shape mobility trajectories through emotions, decisions, knowledge and survival strategies in the "provisional waiting cities.”